COMPARATIVE IN SILICO MOLECULAR DOCKING ANALYSIS OF SOPHOCARPINE AND CHELERYTHRINE ALKALOIDS FOR ANTIHERPES ACTIVITY - Thomas Kurian
Herpes infection is considered a global health burden. Developing new therapeutic strategies for treating herpes is a challenging research problem. This study aimed to investigate and compare the potential antiviral activity of Sophocarpine and Chelerythrine alkaloids against Herpes Simplex Virus Type-1 thymidine kinase in the presence of acyclovir, an established antiviral drug. The study utilized PyRX docking and Auto Dock 4 softwares. The comparative analysis of the docking results showed that both Sophocarpine and Chelerythrine had promising binding affinities, indicating potential antiviral activity. A redocking experiment with acyclovir to test our molecular docking approach confirmed predicted binding modes, validating the reliability of this approach. This is a comparative study of results obtained by two different docking softwares. The results pave the way for further in vitro and in vivo investigation, providing a foundation for developing novel anti-herpes therapeutic agents.